PENDIDIKAN KARAKTER DALAM ALQURAN SURAT ASH-SHAF AYAT 2-3 MENURUT TAFSIR AL-MARAGHI - Masruroh, Duroh Siti; Firdaus, Anis Husni; Millah, Saeful (Bestari, 2018)
The Indonesian nation is facing a multidimensional crisis, the waning of characters that are in accordance with the philosophy of life of the Indonesian nation gave birth to the moral decadence of the nation's generation. Split of personalitty disease (split personality) or inability to unite words and deeds, between theory and practice, has been entrenched almost in every level of society. Education has a role and function to shape the nation's generation. Education can be an arrow to advance a nation so that it competes with other nations, or backfire that can destroy the nation itself. All of that depends on education actors. To build a nation that is able to compete, the quality of human resources is needed that is not only intelligent in its knowledge but also must be a person of character, based on the divinity of the Almighty, and adheres to human values. Therefore, education does not only prioritize cognitive, but education must foster humans to be human beings, human beings who are able to carry out their duties as abdillah and as caliph filard. The method used in this study is the library method (library research), namely by making maximum use of relevant library materials to answer research problems, concepts, principles, theories, doctrines, views and discoveries about character education sought and reviewed from accurate data sources in the field of education related to the problem of this research. Research results show that: Education is not only a means of transferring knowledge, but more importantly education is a place to foster children's character. To shape the character of the nation's generation, all components of education, namely the three centers of education, must actively participate in shaping the character of the nation's generation. In character building, several methods are needed, namely: exemplary methods, habituation, advice and stories, attention and supervision, law and rewards. Alquran verse Ash-Shaff verse 2-3 in its explanation is regarding consistency and integration between one's words and deeds, honest, dare to fight, be responsible and avoid hypocrisy. Education here essentially wants to shape individuals into moral individuals and good character who can live their freedom and responsibilities, in their relationships with others and their world.